Pathogen-Mediated Stomatal Opening: A Previously Overlooked Pathogenicity Strategy in the Oomycete Pathogen Phytophthora infestans - Yang, Li-Na; Liu, Hao; Wang, Yan-Ping; Seematti, Jenifer; Grenville-Briggs, Laura J.; Wang, Zonghua; Zhan, Jiasui (Frontiers in Plant Science, 2021)
Phytophthora infestans, the most damaging oomycete pathogen of potato, is specialized to grow sporangiophore through opened stomata for secondary inoculum production. However, it is still unclear which metabolic pathways in potato are manipulated by P. infestans in the guard cell-pathogen interactions to open the stomata. Here microscopic observations and cell biology were used to investigate antagonistic interactions between guard cells and the oomycete pathogen. We observed that the antagonistic interactions started at the very beginning of infection. Stomatal movement is an important part of the immune response of potato to P. infestans infection and this occurs through guard cell death and stomatal closure. We observed that P. infestans appeared to manipulate metabolic processes in guard cells such as triacylglycerol (TAG) breakdown, starch degradation, H2O2 scavenging and NO catabolism, which are involved in stomatal movement, to evade these stomatal defense responses. The signal transduction pathway of P. infestans induced stomatal opening likely starts from H2O2 and NO scavenging, along with TAG breakdown while the subsequent starch degradation reinforces the opening process by strengthening guard cell turgor and opening the stomata to their maximum aperture. These results suggest that stomata are a barrier stopping P. infestans from completing its life cycle, but this host defense system can be bypassed through the manipulation of diverse metabolic pathways that may be induced by P. infestans effector proteins.